Efficacy of a Recombinant Genotype VII Vaccine against Challenge with Velogenic Newcastle Disease Virus - Yi Cheng; Dongbei Sheng; Xiangdong Li; Sumei Hong; Lixia Guo; Shasha Zhao; Yue Yuan; Jingjing Xue; Hui Tian; Yipin Ren; Wujie Liu; Kegong Tian (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Background: Newcastle disease virus (NDV) genotype VII has become the dominant genotype in China. However, NDV genotype II was used to make current commercial NDV vaccines. The mismatch of genotypes between circulating and vaccine strains of viruses may compromise the efficacy of vaccines. Methods: In this study, a current circulating NDV was attenuated by mutations of multiple basic amino acid motif of fusion cleavage site 112RRQKGF117 based on reverse genetic techniques. The recombinant virus was prepared as an inactivated vaccine to test its efficacy and compared with a commercial LaSota NDV vaccine on SPF chickens. Results: All vaccinated chickens survived by the end of the study. By contrast, the unvaccinated chickens were all dead before 5 days post-challenge (DPC). Compared to commercial LaSota vaccine, the experimental inactivated vaccine elicited earlier and higher titer of HI antibodies and had reduced titer and duration of virus shedding after challenge. Conclusion: The experimental inactivated NDV vaccine may work as a promising vaccine candidate to control the disease.